Hyperfinite construction of G-expectation - Tolulope Fadina; Frederik Herzberg (Bielefeld University, Center for Mathematical Economics (IMW), 2015)
We prove a lifting theorem, in the sense of Robinsonian nonstandard analysis, for the G-expectation. Herein, we use an existing discretization theorem for the G-expectation by T. Fadina and F. Herzberg (Bielefeld University, Center for Mathematical Economics in its series Working Papers, 503, (2014)).
urn:nbn:de:0070-pub-27324854
Keywords: 330; G-expectation; Volatility uncertainty; Lifting theorem; Robinsonian Nonstandard analysis; Hyperfinite discretization